2015
DOI: 10.1517/14712598.2015.1049595
|View full text |Cite
|
Sign up to set email alerts
|

Developing vaccines to prevent malaria in pregnant women

Abstract: The approach taken to develop a P. falciparum erythrocyte membrane protein 1-based vaccine to protect pregnant women is very promising in view of the current difficulties of achieving a sterilizing vaccine against malaria parasite. This approach could help us to control the deleterious effect of malaria infections that characterize severe clinical forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…An effective vaccine against placental malaria should induce broadly active and strain-transcending antibodies to block the adhesion of VAR2CSA-expressing parasites to CSA [81,82]. A single cross-sectional study found that women positive for CSA-binding inhibitory antibodies had significantly decreased odds of placental infection, as well as low birthweight and preterm birth [56].…”
Section: Discussionmentioning
confidence: 99%
“…An effective vaccine against placental malaria should induce broadly active and strain-transcending antibodies to block the adhesion of VAR2CSA-expressing parasites to CSA [81,82]. A single cross-sectional study found that women positive for CSA-binding inhibitory antibodies had significantly decreased odds of placental infection, as well as low birthweight and preterm birth [56].…”
Section: Discussionmentioning
confidence: 99%
“…Women in endemic areas urgently need novel interventional methods. In areas of stable transmission, the prevalence and severity of placental malaria diminish with successive pregnancies [ 5 , 6 ] demonstrating that immunity is acquired as a result of natural infection, and supporting the prospects for a vaccine that protects pregnant women and their children from the dire consequences of placental malaria [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Placental malaria constitutes a large problem in malaria endemic countries and current control strategies based on the administration of repeated curative doses of antimalarial treatment (intermittent preventive treatment during pregnancy, IPTp) during the 2 nd and 3 rd trimester are compromised by development of parasite drug resistance and a general low effective delivery of IPTp programme in sub-Saharan African countries. IPTp also suffers from the inherent problem that the first treatment dose is often given after the initial exposure to malaria and irreversible damage to the placenta has already occurred [ 33 ]. An effective vaccine protecting women against PM infection would circumvent these problems.…”
Section: Discussionmentioning
confidence: 99%